Pelatihan Dan Pendampingan Sistem Informasi Manajemen Di Era New Normal - Ni Luh Putu Sariani; Ni Made Satya Utami Satya Utami (UNUSA Press, 2021)
Bali has a charm nature, unique culture that captivated the hearts of foreign tourists and domestic to visit. Since the pandemic covid-19 struck the world, economic growth in Bali the year 2020 has decreased, because one of the economic incomes of the business sector tourism. Efforts The government Bali restore the economy, turn on the micro, small and medium Enterprises (SMES). Peken Facebook is the SMES take the opportunities businesses trading through online networks and social media that continues to innovate using digital technology in the pandemic covid-19. Based on observation and interview found a weakness, the absence of application of Management Information System (SIM) the better. The purpose for apply SIM in the running of the operational business Peken Facebook so the quality of services increased as well as customer satisfaction achieved. Methods the activities of socialization, provides training and the practice of direct application of SIM and mentoring. The results of the activity show the high enthusiasm of the participants, Peken Facebook apply SIM in the running of their business operations to support service activities to meet the needs of the consumer. Conclusion, the service is done to increase the quality of human resources and partnerships, understand the concept of SIM as well as can give the satisfaction of consumers. Advice, Peken Facebook expected can apply the SIM properly, perform the evaluation in accordance with the development of market conditions so that it can create, innovate, following the development of better technology, particularly in terms of the provision of excellent service to the consumer.